Transformation of the Science Curriculum in Iceland - Meyvant Þórólfsson 1951- (2013)
This doctoral thesis is primarily based on a compilation of research articles on the transformation of the science curriculum in Icelandic compulsory schools from 1960 to 2010. The problem addressed in the thesis is the transformation of the science curriculum. It embodies the proposition that science education ‘transforms’ constantly, entailing constant conjunction and deliberation between distinct ideologies and curriculum models. The idea of ‘transformation’ indicates that the science curriculum evolves and reflects a state of perpetual flux rather than fixity. Thus it was assumed that not only the official curriculum reflected constant changes; it also implied constant evolvement, ongoing and indivisible, of the implemented curriculum. Concepts from language studies, ‘diachrony’ and ‘synchrony’, were borrowed for further elaboration, where diachrony implies studying changes of the science curriculum over time and synchrony means studying its operation concurrently in various contexts. Thus the study sought answers to the following questions: What characterised the transformation of the science curriculum for Icelandic compulsory schools in force from 1960 to 2010: a) from a diachronic perspective? b) from a synchronic perspective? The thesis comprises three sets of research data and findings, first three articles based largely on documentary analysis about the transformation of the science curriculum, secondly two articles based on interviews and on-site observations with science teachers, thirdly practitioner-researcher data. The findings imply that natural science, as a curricular field, proves to be dynamic in nature. Transient ideologies, traditions and curriculum models seem to mix regarding both policy and practice. Furthermore, the science curriculum appears increasingly as a ʿcrowded placeʾ, where new ideas and information have an easy access, but prior ideas and systems tend to remain and amalgamate with new ones, resulting in a curriculum that transforms into a ʿkaleidoscopic quiltʾ. Practitioners, ...